Er: YAG Laser and Dermabrasion Treatment in Facial Rejuvenation - AYGIT, A. Cemal; BENLİER, Erol and TOP, Hüsamettin (Cerrahpaşa Medical Journal, 2014)
The facial wrinkles, hyperpigmentation and post-acne scars are the most common causes of facial rejuvenation. Facial rejuvenation can be done with dermabrasion, laser or chemical peeling. Thirty-eight cases were included in this study. Between September 1999 and January 2004, full face Er: YAG laser was performed in 28 cases and dermabrasion was performed in 10 cases. Mean age of cases was 32 ± 2.3 ( 6 - 49 ). Twenty-six cases were female, other 12 were male. Laser treatment was performed due to facial wrinkles in 18 cases which had Fitzpatrick skin type between II and V, due to acne scars in 14 cases and in 6 cases had hiperpigmentation areas on their faces. Er: YAG laser was used with a 2,5 mm handpiece at the setting of 8-20 J / cm2 . Dermabrasion was performed with motor or sterilized sandpaper. Although the results of Er: YAG application were satisfied in cases with fine wrinkles in lighter type skin, it was not effective in cases that had deep wrinkles and post-acne scars. Hyperpigmented skins which were treated Er: YAG laser have been shown some recurrence. We concluded that dermabrasion was more effective tool for surgeons in facial rejuvenation, because depth of skin abrasion was easily controlled. Benlier E, Top H, Aygıt C. A.